Tales from the global economy the Cappucino trail - Newson, Jeremy; British Broadcasting Corporation ([S.l.] : BBC Active, 2006)
By following the trail of two coffee beans grown in the Peruvian Andes, this program looks at the stimulant, which, after oil, is the most globally traded commodity. One of the beans takes the route of the open market where its price is determined by commodities traders and analysts. The other bean finds its way into a gourmet coffee made by a company dedicated to paying fair prices to farmers for their high-quality organic crop
Title from title screen
Executive producer, Gina Newson ; editor, Alana Smith ; sound, Mick Duffiels, Maria Elena Melgar, Marshall Woodall ; camera, Julian Zacarias...[et al.]
Keywords: Coffee industry -- Economic aspects; Coffee growers -- Economic conditions; Globalization; International economic relations